1977
DOI: 10.1088/0022-3727/10/4/009
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of semiconductor light-emitting diodes, high-radiance lamps and lasers

Abstract: Detailed experimental results and suggested theories on the degradation of light-emitting diodes (LEDS), high-radiance lamps and semiconductor lasers are reviewed. Experimental results on LEDS show that a number of light-degrading mechanisms can operate which probably include migration of impurities or point defects. Dislocations when present in high densities also give rise to degradation in LEDS. Extrapolated lives to half intensity of between lo5 and lo7 h have been commonly projected for these devices, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
2

Year Published

1978
1978
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 42 publications
1
1
0
2
Order By: Relevance
“…Reliability studies of VCSELs have found that defects are mainly confined inside the active region, which may likely be due to the built-in strain in the quantum well and/or barrier and the heat generated by the high carrier density as they collide with the lattice and recombine non-radiatively [28], [29]. Our experimental observations also support this finding.…”
Section: B Reduced Two-dimensional Equationsupporting
confidence: 81%
“…Reliability studies of VCSELs have found that defects are mainly confined inside the active region, which may likely be due to the built-in strain in the quantum well and/or barrier and the heat generated by the high carrier density as they collide with the lattice and recombine non-radiatively [28], [29]. Our experimental observations also support this finding.…”
Section: B Reduced Two-dimensional Equationsupporting
confidence: 81%
“…[4][5][6] The degradation of light emitting diodes is a multi-faceted problem that involves change of defect population, catastrophic optical destruction, metal diffusion and electrode delamination. 7 It is an elusive subject for research due to the presence of difficulties in identifying a specific degradation mechanism in different types of LEDs. In fact, different causes may dominate even in a single type of diode, and different degradation mechanisms can be observed simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1. -Evolution typique de la durée de vie moyenne des lasers dans la période de 1970-1978. [Trend in the useful life of lasers over the period [1970][1971][1972][1973][1974][1975][1976][1977][1978] [22]. ]…”
unclassified
“…The scales along the ordinate can vary over hours to tens of thousands of hours [22].] Cet effet s'observe également sur les caractéristiques, puissance lumineuse émise en fonction du courant direct appliqué, relevées à des stades différents de la dégradation.…”
unclassified